2016
DOI: 10.1093/nar/gkw480
|View full text |Cite
|
Sign up to set email alerts
|

A novel role for poly(C) binding proteins in programmed ribosomal frameshifting

Abstract: Translational control through programmed ribosomal frameshifting (PRF) is exploited widely by viruses and increasingly documented in cellular genes. Frameshifting is induced by mRNA secondary structures that compromise ribosome fidelity during decoding of a heptanucleotide ‘slippery’ sequence. The nsp2 PRF signal of porcine reproductive and respiratory syndrome virus is distinctive in directing both −2 and −1 PRF and in its requirement for a trans-acting protein factor, the viral replicase subunit nsp1β. Here … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
73
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(77 citation statements)
references
References 59 publications
4
73
0
Order By: Relevance
“…Deviations in the downstream element were rare and did not involve more than one nucleotide, while observed sizes of Ϫ2TF domains were comparable (with the exception of LDV L13298.1 47 aa -2TF domain) to the experimentally verified size of the Ϫ2TF domain of PRRSV (Table 4). These results suggest that the observed variations in PRF motifs in our large virus data set (Table 4) may be compatible with their function despite the detrimental effects of some of these variations artificially introduced into PRRSV-2 (33,35).…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…Deviations in the downstream element were rare and did not involve more than one nucleotide, while observed sizes of Ϫ2TF domains were comparable (with the exception of LDV L13298.1 47 aa -2TF domain) to the experimentally verified size of the Ϫ2TF domain of PRRSV (Table 4). These results suggest that the observed variations in PRF motifs in our large virus data set (Table 4) may be compatible with their function despite the detrimental effects of some of these variations artificially introduced into PRRSV-2 (33,35).…”
Section: Resultssupporting
confidence: 58%
“…Their generation involves Ϫ1 and Ϫ2 PRFs in the nsp2 genome region encoding the HVR-TM1 junction and is directed by a slippery sequence and a downstream C-rich element conserved in several arteriviruses but not EAV (33,34). PRFs are transactivated by a complex of viral nsp1b and host poly(C) binding protein (PCBP) that binds to the downstream C-rich element (34,35).…”
mentioning
confidence: 99%
“…We can now confirm that this effect is mediated at the translational level, and depends on protein-stimulated PRF rather than ribosomal drop-off at StopGo or at other sites during polyprotein synthesis. Together with À 2 PRF for nsp2TF expression in members of the family Arteriviridae, where we recently demonstrated that PRF is critically dependent on the arteriviral protein nsp1b and host poly(C) binding proteins interacting with a 3 0 C-rich motif separated from the frameshift site by a 10-nt spacer 27 , this is one of only two known cases of protein-stimulated PRF. As 2A and nsp1b are viral proteins, they cannot be utilized for normal cellular gene expression.…”
Section: Discussionmentioning
confidence: 89%
“…Some RNA viruses naturally employ viral and cellular encoded proteins to regulate PRF during viral replica-tion cycles. For example, a novel Ϫ1/Ϫ2 PRF mechanism is stimulated in the absence of any apparent downstream RNA structural element in porcine reproductive and respiratory syndrome virus (23,24). Both Ϫ1 and Ϫ2 PRF events are stimulated by the binding of a trans-acting protein complex composed of the virus-encoded nsP1␤ replicase subunit and the cellular poly(C)-binding protein.…”
Section: Employing Trans-acting Modulators To Make Variable Resistorsmentioning
confidence: 99%